Advances in application of swept-source optical coherence tomography angiography in diagnosis and treatment of diabetic retinopathy - Zhang, Jinyan; Huo, Qianqian; Xia, Deyu; Wang, Mingfang; Li, Xiuyun (Frontiers in Ophthalmology, 2023)
Diabetic retinopathy (DR) is the most common microvascular complication of diabetes and one of the leading causes of global blinding. More attention should be paid to the diagnosis, treatment and prognosis of DR. Swept-source optical coherence tomography angiography (SS-OCTA) is a novel imaging technique presented in recent years. It can accurately present the various levels of the retina, choriocapillaris, macula, and the optic papillary microcirculation, which is new to the diagnosis and prognosis of DR. The present study reviews the advances in clinical application of SS-OCTA in diagnosis, treatment and prognosis of DR.